PENGEMBANGAN KAWASAN WISATA BERBASIS PARTISIPASI MASYARAKAT LOKAL DI DESA KAHAYYA KABUPATEN BULUKUMBA - Rahman Sannu; Buyung Romadhoni; Amelia Rezky (COMPETITIVENESS, 2021)
This research aims to analyze governance policies and the role of the community in the development of tourist areas conducted by the Bulukumba District Cultural and Tourism Office and formulate a model for the development of participation-based tourist areas in Kahayya Village, Kindang District, Bulukumba Regency. The problem in this study is that the management of tourism governance in Bulukumba Regency has not experienced a significant increase in the number of visitors. The low number of visits can be due to a less professional, transparent, accountable, and un-integrated governance system and inadequate infrastructure transparency. This method uses quantitatitive research. The results showed that: 1) Policies carried out by the Bulukumba District Cultural and Paratourism Office in the governance of Kahayya Village Natural Tourism Area included cooperation with several communities, approaches to the community in the creative economy, and formed RIPPDA (Regional Tourism Planning Master Plan) in 2009. 2) Kawadan tourism needs to be managed properly by collaborating with cuttingholders for the development of the tourism sector including the Natural Tourism Area in Kahayya Village. 3) Several development models that need to be done for the development of tourist areas in Kahayaa Village of Kindang District of Bulukumba Regency, namely cultural elements need to be maintained in the development of natural tourism areas in Kahayya Village to attract tourists visiting Kahayya Village, creating new innovations such as tour guides involving the surrounding community in Kahayya Village, utilizing social media and also collaborating with millennial figures to promote tourist areas.  Nature in Kahayya Village and does not build luxury facilities such as hotels and other facilities that can change the nuances of nature in the natural tourist area in Kahayya Village. Keywords: Policy, Role of Society